FREE HEALTH CHECK ACTIVITY PROGRAM IN SAMARINDA ILIR DISTRICT, SAMARINDA CITY - Iskandar Iskandar (Open Edutech Indonesia, 2025)
Free health check-up is one component of community service activities carried out in Samarinda Ilir District which aims to increase public understanding of the importance of carrying out routine health checks to detect non-communicable diseases. This activity was attended by 77 participants, who underwent blood pressure and blood sugar checks. The results showed that the participants were very enthusiastic about following this health check-up in an orderly manner, the results of the health check-up were half of the participants did not have hypertension, 50 people (64.9%), while 27 people (35.1%) had hypertension and half of the participants had blood sugar <100 - 125 mg / dl, 61 people (79.2%), while 16 people (20.8%) had blood sugar ˃ 126 mg / dl. Based on the results of this health check-up, it can be concluded that it increases public understanding to carry out regular health checks to detect non-communicable diseases